RESPONSABILIDAD FAMILIAR Y ASISTENCIA SOCIAL, EN LAS NIÑAS CON DISCAPACIDAD DEL HOGAR “SAN CAMILO DE LELLIS DE LA CIUDAD DE LOJA” Y EL ACCIONAR DEL TRABAJADOR SOCIAL - Sandoval Jaramillo, Nataly Alexandra (2019)
This research entitled family responsibility and social assistance, in girls with disabilities of the home "San Camilo de Lellis of the city of Loja" and the actions of the social worker, is based on a study of parents and assistance social to girls with disabilities of the Home. The general objective of the research is to contribute with a proposal focused on strengthening family responsibility and social assistance, for girls with disabilities in the “San Camilo de Lélis de la Loja” home and the actions of the social worker. The specific objectives of the investigation allowed a diagnosis in the San Camilo de Lellis Home on family abandonment and social assistance of the State to girls with disabilities, to analyze the information obtained on family abandonment and social assistance of the State to girls with disabilities and develop a proposal focused on strengthening family responsibility and social assistance for girls with disabilities. Regarding the methodology, the scientific, inductive, deductive, analytical and descriptive method was used for the purpose of verifying, concluding, detailing, analyzing and describing all the information obtained in the research process. In the same way, techniques such as observation, interview, survey, socio-economic records and graffar method were used, which were used to gather information regarding alternatives to foster this family responsibility. The present study had the participation of 5 parents who visit the girls, the staff that works and the one that lives in the home, the methodology used was based on the methods the methods scientific, inductive, deductive, and descriptive, by The use of techniques. The main findings obtained in the investigation, establish that the responsibility of the family with a person with disabilities is not fully fulfilled. Girls with disabilities require care that is not always given due to poor staffing, and all physical spaces are not easily accessible for girls with 5 disabilities feeling incapable and insecure of themselves, preventing them from having adequate integral development due to their lack of affect. The role of the Social Worker is of great importance in the improvement of family responsibility and social assistance to girls with disabilities, so an action plan focused on strengthening family responsibility and social assistance for girls with Disability of Hogar San Camilo de Lellis and the professionals in charge of girls with disabilities execute the activities of the action plan.